2003
DOI: 10.1007/s11745-003-1063-3
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro method for studying the proliferation and differentiation of Atlantic salmon preadipocytes

Abstract: The aim of the present study was to develop a cell culture system for studying the proliferation and differentiation of preadipocytes isolated from Atlantic salmon adipose tissue. The expression of proliferating cell nuclear antigen (PCNA) was used as a marker for cell proliferation. The cells started to proliferate within 48 h after seeding and continued to proliferate throughout the culture period of 2 wk. Undifferentiated preadipocytes showed a fibroblast-like morphology with a homogeneous cytoplasm devoid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
91
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(107 citation statements)
references
References 26 publications
(23 reference statements)
14
91
1
1
Order By: Relevance
“…The data was obtained using an antiserum raised against mammalian leptin; nevertheless, the performed controls confirmed the specificity of the immunostaining (the antiserum pre-incubated with its specific antigen gave negative results) and the consistent molecular weight of the immunodetected protein. In fact, Western blot analysis showed a 16-kDa band comparable to those previously obtained in various vertebrates (Johnson et al 2000;Vegusdal et al 2003;Neglia et al 2008). Leptin amino acid sequence is conserved in mammalian and fish classes even though it seems to show higher diversity within teleosts (Kurokawa et al 2005).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The data was obtained using an antiserum raised against mammalian leptin; nevertheless, the performed controls confirmed the specificity of the immunostaining (the antiserum pre-incubated with its specific antigen gave negative results) and the consistent molecular weight of the immunodetected protein. In fact, Western blot analysis showed a 16-kDa band comparable to those previously obtained in various vertebrates (Johnson et al 2000;Vegusdal et al 2003;Neglia et al 2008). Leptin amino acid sequence is conserved in mammalian and fish classes even though it seems to show higher diversity within teleosts (Kurokawa et al 2005).…”
Section: Discussionsupporting
confidence: 68%
“…However, to date, only a few studies concerning the localisation of leptin in bony fish can be found and most of them only refer to adults (Johnson et al 2000). Leptin was immunodetected in the blood, brain, heart and liver of several bony fish species (Johnson et al 2000), in the enteric epithelium and nervous system of trout (Muruzàbal et al 2002) and in salmon adipocytes (Vegusdal et al 2003). Furthermore, leptin expression has been found in liver, adipose tissue, ovary and pituitary gland (Kurokawa et al 2005;Huising et al 2006;Gorissen et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A protocol for studying the proliferation and differentiation of these cells in Atlantic salmon adipose tissue has been described (Vegusdal et al 2003). These authors observed that PPARg, C/EBP, and leptin were expressed in mature adipocytes grown in culture, as shown for mammals, and the supplementation of 10% of fetal bovine serum (FBS) to the culture medium did not affect pre-adipocyte differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…In mammals, primary cell cultures have contributed to unraveling the major processes involved in adipogenesis, such as the proliferation of precursor cells and the differentiation of these cells into adipocytes. This type of culture system has been developed only in two fish species (Vegusdal et al 2003, Oku et al 2006. Nevertheless, from the data obtained in mammals, it can be concluded that factors that regulate adipogenesis differ considerably between species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation